JUDEX FACTI MAHKAMAH SYAR’IYAH PROVINSI ACEH DALAM MENANGANI PERKARA CERAI TALAK (Analisis Putusan Nomor 45/Pdt.G/2017/MS.Aceh) - H Hidayatullah; H Burhanuddin (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2020)
The judiciary is organized into two levels, the first level of justice is Religious Court/Syar'iyah Court, and the court of appeal is the Religious High Court/Provincial Syar'iyah Court. These two trials are referred to as judex facti. The judex facti function is carried out through several stages, is: formulating facts, looking for cause and effect relationships and figuring out probabilities. So, the background of this research is related to the application of judex facti in Aceh Syar'iyah Court. Based on the analysis of the data carried out, it is concluded that the Judex Facti of the Aceh Syar'iyah Court in trying and deciding divorce case Number 45/Pdt.G/2017/MS.Aceh has tried to apply in accordance with the principles of law and legislation in force. That is in the ruling the Aceh Syar'iyah Court panel of judges had given maximum consideration to the reasons for the comparison in filing an appeal. However, there are still shortcomings and anomalies related to the reasons for the comparison in submitting a request so that the 10-grand dowry that has not been paid in full is not granted by the panel of judges of the Syar'iyah Court. Because of this, the judiciary of the Aceh Syar'iyah Court was judged to have shortcomings and was not optimal in applying the law. Although in authority the panel of judges may not grant the demands of the comparator as long as they do not conflict with applicable laws and regulations. If judged from the whole, the judex facti of the Aceh Syar'iyah Court has implemented it in accordance with the applicable laws and regulations.